Grafting-Induced Phenotypic and Genomic Variations in Cassava (Manihot esculenta Crantz) through Interspecific Compatibility with M. Glaziovi - Ulfa, Umi Tahniah; Sudarsono, Sudarsono; Ardie, Sintho Wahyuning; Mulyaningsih, Enung Sri; Hartati, N. Sri; Anjarsari, Nurul Aeni; Dewi, Prita Sari (Journal of Tropical Crop Science, 2025)
Grafting is a promising approach to enhance cassava (Manihot esculenta Crantz) productivity, particularly in improving tuber yield and quality. Despite its technical simplicity, research on the morphological and molecular consequences of grafting in cassava is limited. This study aimed to quantitatively assess phenotypic differences between grafted and shoot cutting plants and characterize genetic modifications in shoot apical meristems near the graft union. Three splice-grafting combinations were evaluated: M. glaziovii (cv. "Karet")/"Revita RV1" (KR), "Karet"/ "Carvita 25" (KC), and "Carvita 25"/ "Revita RV1" (CR), alongside shoot-cutting plants of each cultivar. Grafted seedlings and conventional cuttings were transplanted to the field, and growth was monitored up to five months after grafting (5 MAG). Shoot bud samples were collected for RAPD analysis at three months (3 MAG). Grafted plants showed differences in morphology compared to controls, especially in branching architecture, branch angle, stem diameter, and internode length. However, the overall plant form and primary stem type remained stable. The color of emerging shoots consistently reflected their genotypic origin, like scion or rootstock, as did the shoot buds nearest the graft union. RAPD analysis using multiple primers revealed polymorphic banding patterns, with OPE-12 producing the most diverse profiles. While specific bands were associated with each cultivar, grafted regenerants often exhibited altered or novel band profiles, suggesting somaclonal variation or graft-induced genetic/epigenetic changes. Some regenerants displayed unexpected band types, such as C1 in R-KR1 and R-KR3, which were absent from their known parental genotypes. Cluster analysis grouped 45 samples into five major clusters and eight subgroups, indicating genetic divergence among certain grafted combinations, particularly "Carvita 25"–"Revita RV1" and M. glaziovii–"Revita RV1". These results demonstrate that grafting can significantly impact cassava phenotype and genome stability. This study shows that interspecific grafting between cassava (Manihot esculenta Crantz) and M. glaziovii can induce significant phenotypic and genomic variations.